Struktur dan Kaidah Kebahasaan Teks Eksplanasi Siswa Kelas VII SMP Negeri 7 Pariaman - Sari, Ratih Ratna; Zuve, Farel Olva (Indonesian and Regional Language and Literature Department, Universitas Negeri Padang, 2024)
Writing skills are an intellectual activity of a person in pouring ideas or ideas that are in his mind through written language. This study aims to analyze the structure and linguistic rules of the explanatory text of seventh grade students of SMP Negeri 7 Pariaman. This type of research is qualitative research. The method used in this research is descriptive method. The source of data in this study is an explanatory text by class VIII students of SMP Negeri 7 Pariaman in the 2023/2024 school year, which is an instrument or research tool is a person or human instrument, namely the researcher himself. Based on the results of the study, it can be concluded that the structure and linguistic rules in the explanatory text of class VIII students of SMP Negeri 7 Pariaman are still lacking. Judging from the language, the use of causal conjunctions is good, the use of chronological conjunctions is lacking, the use of prepositions is lacking, the use of capital letters is lacking, the use of comma punctuation is lacking, and the use of standard words is good.